Exploring the Temporality of Complex Computational Practice: Two Eclipse Notes by John of Murs in the ms Escorial O II 10. (February 2016) - Husson, Matthieu
Abstract: Manuscript Escorial O II 10 is a late 13th‐century document containing a well‐known collection of astronomical texts from the arts faculty context. During the first half of the 14th century, this manuscript belonged to John of Murs, an important master of art of the Paris University, responsible, with others for the establishment of the Parisian Alfonsine Tables. John of Murs used the Escorial manuscript to record a wide range of notes over a 20‐year period. Among those notes I examine here one concerned with two solar eclipses. Although I will review the relevant information concerning eclipse theory and mathematical practices of European astronomers in the 14th century, this essay will not focus directly on such matters. Rather I am interested in a documentary question: looking at a specific astronomical source I seek clues about the temporal dimensions of a computation as it was recorded in the codex. This focus will help assess the computation practices of John of Murs and will allow an understanding of the meanings such a computational record could have both for its author and in the more general context of early Alfonsine astronomy.